A global catalog of Martian impact craters with actual boundaries and degradation states - Liu, Danyang; Cheng, Weiming; Qian, Zhen; Liu, Jia; Liu, Jianzhong; Wang, Xunming (International journal of applied earth observation and geoinformation, 2024)
•A global catalog of Martian craters with actual boundaries is proposed using deep learning and manual visual inspection.•A global assessment of degradation states is realized using an index system of morphological attributes.•The natural breaks method of slope and K-means++ clustering are used to classify craters as flat or bowl-shaped craters. Martian impact craters record the modifications of fluvial, wind, and glacial forces, which are crucial for studying the resurfacing of Martian terrain. To the best of our knowledge, current global catalogs of Martian craters, represented as circles, contribute to dating the age of the planetary surface. However, these recorded circles may not meet the increasing requirements of degradation states assessment, rover navigation, and geomorphological and geological mapping, which rely on the actual boundaries of craters. Additionally, the existing Martian crater catalogs provided a regional degradation state of craters based on time-consuming manual assessment. To overcome these gaps, we proposed a global Martian crater catalog that records craters’ actual boundaries and degradation states. Construction of the catalog involved deep learning and manual inspection to efficiently delineate the actual boundaries. On the basis of these actual boundaries, we calculated 19 attributes, including morphological attributes and degradation states. Specifically, the crater shapes were classified into flat and bowl-shaped types by dividing the slopes of the crater bottoms and the walls. According to the erosion process, the state of degradation was classified into three classes: fresh, partly buried, and subdued. Degradation state was assessed globally using the random forest method and explained by the SHapley Additive exPlanations (SHAP) model. The distribution of partly buried craters indicated the relationship between the degradation state and the valley networks. This catalog could be applied in further research on Martian terrain degradation, valley network erosion, and deep space exploration. Our catalog and the benchmark dataset of degradation state will soon be made publicly available at https://zenodo.org/records/11514787.